Analysis of Economic and Environmental Benefits of Green Business Practices in the Hospitality and Tourism Sector - Siti Kholijah (Involvement International Journal of Business, 2024)
This research presents an analysis of the economic and environmental benefits resulting from the adoption of green business practices in the hospitality and tourism sector. The study explores the growing significance of sustainability in this industry and investigates the specific findings and advantages associated with embracing environmentally friendly practices. By conducting a comprehensive review of pertinent literature, incorporating case studies, and examining empirical evidence, this article provides valuable insights into the potential economic and environmental benefits of green practices in the hospitality and tourism sector. The analysis reveals that green business practices in the hospitality and tourism sector can lead to substantial cost savings and improved operational efficiency. Implementation of energy and resource management strategies, such as energy-efficient lighting, water conservation measures, waste reduction, and sustainable procurement, can result in reduced operational costs and enhanced overall efficiency. Furthermore, the study finds that adopting green practices can generate new revenue streams and differentiate businesses in the market. Effective eco-friendly branding and marketing strategies attract environmentally conscious consumers, leading to increased customer loyalty and potential revenue growth. The analysis also uncovers the positive environmental impacts of green practices, including reduced carbon emissions, waste generation, and resource consumption. Measures like renewable energy adoption, waste recycling, and water conservation contribute to a reduced carbon footprint, conservation of natural resources, and preservation of local ecosystems and biodiversity. Governmental support and incentives are identified as crucial drivers in the adoption of green business practices in the hospitality and tourism sector.